The ethnic eye : Latino media arts - Noriega, Chon A., 1961-; López, Ana M. (University of Minnesota Press, 1996)
This groundbreaking volume is the first to examine the range of Latino media arts, from independent feature production to documentary to experimental video. The essays explore the work of Chicano, Puerto Rican, Cuban American, and Latino film and video artists and address avant-garde practices, queer media, and performance art, as well as more conventional film and video representations.